Water-vapor-resistant refractory material for glass melting furnace and preparation method of water-vapor-resistant refractory material
By modifying the combination of materials such as electromelted magnesium aluminum spinel and nanotitanium dioxide, refractory materials for glass melting kilns with high thermal shock resistance, corrosion resistance and low thermal conductivity were prepared, which solved the problem of insufficient performance of existing refractory materials under high temperature and temperature changes, and achieved more efficient use and lower energy consumption.
Patent Information
- Application Number
- CN202411970849.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing refractory materials have insufficient thermal shock resistance when facing high temperatures and drastic changes in temperature, which is prone to cracks, and their performance decreases under chemical corrosion of molten glass, which increases the maintenance cost of glass kilns, and at the same time, excessive thermal conductivity leads to increased energy consumption.
The combination of modified electromelted magnesium-aluminum spinel, modified nano-titanium dioxide, aluminum titanate, scandium-oxide stable zirconia, nano-silicon carbide, nano-alumina, zirconite powder and polyvinyl alcohol solution was prepared by ball milling and pressing and insulating treatment at high temperature to prepare a refractory material for glass melting kiln that resistant to water vapor was prepared.
It significantly improves the thermal shock resistance, corrosion resistance and low thermal conductivity of refractory materials, extends the service life of the material, reduces energy consumption, and improves the efficiency of glass kilns.
Smart Images

Figure CN119751042A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a water vapor resistant refractory material for a glass melting furnace and a preparation method thereof. Background Art
[0002] The production of glass relies on the high-temperature melting of raw materials such as quartz sand and soda ash in glass kilns, which poses severe challenges to the refractory materials used in glass kilns, including multiple challenges such as withstanding high temperatures, corrosion, and thermal conductivity. Although existing refractory materials perform well in terms of strength and corrosion resistance, they are not resistant to thermal shock when faced with drastic temperature changes, and are prone to cracking when the temperature changes sharply, which affects their service life; refractory materials are prone to chemical erosion when chemically corroded by molten glass, resulting in a gradual decline in material performance and an increase in the maintenance cost of glass kilns; many refractory materials also have the problem of excessively high thermal conductivity, which can lead to rapid heat transfer, increase energy consumption, and reduce thermal efficiency. Therefore, the development of a refractory material with stronger thermal shock resistance, corrosion resistance, and low thermal conductivity has become an urgent need to improve the efficiency of glass kilns. Summary of the invention
[0003] In view of this, the purpose of the present invention is to overcome the above-mentioned technical deficiencies and provide a refractory material for a glass melting furnace that is resistant to water vapor and a preparation method. The refractory material prepared by this method has stronger thermal shock resistance, corrosion resistance and low thermal conductivity.
[0004] In the first aspect, the technical solution adopted by the present invention to solve the above technical problems is:
[0005] A water vapor resistant refractory material for a glass melting furnace. The refractory material comprises, by weight: 15-20 parts of modified fused magnesia-aluminum spinel, 5-8 parts of modified nano titanium dioxide, 15-20 parts of aluminum titanate, 10-15 parts of scandium oxide stabilized zirconia, 10-15 parts of nano silicon carbide, 5-10 parts of nano alumina, 10-20 parts of zircon powder and 3-5 parts of polyvinyl alcohol solution.
[0006] Further: The preparation method of the modified fused magnesium aluminate spinel is as follows: 14g of flake graphite, 2.5g of Al-Si alloy powder and 2g of sodium tripolyphosphate are put into a ball mill and mixed for 30min, 83.5g of fused magnesium aluminate spinel is added and mixed in a high-speed mixer for 20min, 8.5g of phenolic resin and 0.6g of urotropine are added and mixed for 15min, and the mixture is placed in a 60°C vacuum drying oven for drying until the volatile content is controlled between 0.85% and 0.95%, thereby obtaining the modified fused magnesium aluminate spinel.
[0007] Further: the preparation method of the modified nano titanium dioxide is as follows: 170 mL of tetrabutyl titanate is slowly added dropwise to 830 mL of anhydrous ethanol, and then 1.86 g of ferrocene is added. The addition of tetrabutyl titanate and ferrocene is completed on a magnetic stirrer until the mixture is stirred evenly to obtain a solution A; in a flame spray pyrolysis reactor FSP, the gas flow rates are adjusted to be: H 2 5.3 L / min, O 2 5.0L / min, air 11.9L / min, and solution A was delivered at 5.0mL / min. After ignition, it burned in a hydrogen-oxygen flame to prepare modified nano-titanium dioxide.
[0008] In a second aspect, the present invention provides a method for preparing a water vapor resistant refractory material for a glass melting furnace, the preparation method comprising the following steps:
[0009] S1. Weigh the raw materials in the above technical solution by weight and set aside;
[0010] S2, putting the modified fused magnesia-aluminum spinel, modified nano titanium dioxide, aluminum titanate, scandium oxide-stabilized zirconium oxide, nano silicon carbide, nano alumina, and zircon powder weighed in step S1 into a ball mill and mixing them evenly, adding the polyvinyl alcohol solution and mixing them thoroughly in a low-speed mixer to obtain a mixture;
[0011] S3, pouring the mixture into an isostatic press under 120 MPa conditions, pressing and molding, and drying to obtain a green body;
[0012] S4. Heat-treating the green body at 1600-1800°C for 6-8h to obtain the final refractory material.
[0013] Preferably: in step S2 of the present invention, the speed of mixing the raw materials in the ball mill is 300 rpm and the time is 1-3 hours.
[0014] Preferably, the materials are trapped for 3-4 hours after being mixed evenly in step S2 of the present invention. The purpose of trapping is to make the raw materials mix more evenly, which is very important for ensuring the uniform structure and performance of the refractory material.
[0015] Preferably, the drying temperature in step S3 of the present invention is 150° C. and the drying time is 6 hours.
[0016] Preferably, in step S3 of the present invention, the material is cured at room temperature for 20-24 hours after drying. The purpose of curing at room temperature is to improve the stability of the material structure to ensure durability during subsequent use.
[0017] Preferably, in step S4 of the present invention, the heating rate during heating is 4°C / min, and the cooling rate is 3°C / min.
[0018] Preferably: the heat treatment process in step S4 of the present invention needs to be carried out under nitrogen protection.
[0019] The present invention has the following beneficial effects:
[0020] 1. The modified fused magnesium aluminum spinel in the present invention shows significant advantages in performance, which are mainly reflected in corrosion resistance, high temperature resistance, thermal shock stability and mechanical properties. By introducing ingredients such as sodium tripolyphosphate and boron glass powder, the modified fused magnesium aluminum spinel improves its corrosion resistance to high-temperature molten glass and other corrosive media, inhibits surface corrosion and structural degradation of materials caused by chemical reactions in high-temperature environments, and extends the service life of the material. The addition of flake graphite and Al-Si alloy powder improves the stability of the material under extreme high temperature conditions, reduces the generation and expansion of cracks caused by thermal stress, improves the thermal shock resistance of the material, and ensures the long-term reliability of the material in a working environment with severe temperature fluctuations. In addition, the crystal framework of the modified fused magnesium aluminum spinel is very tight and stable, so that the material can still maintain structural integrity under high temperature and water vapor environment. Therefore, the modified spinel also has a good water vapor resistance effect. Modified fused magnesia-alumina spinel is optimized in many aspects such as high temperature, corrosion, water vapor resistance, and thermal shock performance, making it an ideal refractory raw material for high temperature and harsh working conditions such as glass kilns, meeting the higher requirements of modern industry for the performance of refractory raw materials.
[0021] 2. The advantages of the modified nano-titanium dioxide in the present invention are mainly manifested in that iron doping can effectively adjust the electronic structure of nano-titanium dioxide and promote the improvement of its catalytic activity and thermal stability. In refractory materials, iron-doped nano-titanium dioxide enhances the thermal shock resistance of the material and improves its corrosion resistance and mechanical strength in high-temperature environments. This doping modification enables the material to maintain better structural stability under extreme temperature changes, reduces crack propagation and rupture caused by thermal stress, and improves the durability of the material in high-temperature and highly corrosive media. Therefore, the addition of modified nano-titanium dioxide effectively improves the comprehensive performance of refractory materials and expands its application prospects in high-temperature industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a comparison chart of the thermal shock resistance of refractory materials of Example 1-3 and Comparative Example 1-3.
[0023] Figure 2 It is a comparison chart of thermal conductivity of refractory materials of Example 1-3 and Comparative Example 1-3.
[0024] Figure 3 It is a comparison chart of the corrosion resistance of refractory materials of Example 1-3 and Comparative Example 1-3. DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. Fused magnesium aluminum spinel was purchased from Henan Fengkai Refractory Materials Co., Ltd., tetrabutyl titanate was purchased from Shandong Huayao Biotechnology Co., Ltd., ferrocene was purchased from Shandong Maofa Chemical Co., Ltd., flake graphite was purchased from Lingshou County Shifeng Mining Processing Plant, Al-Si alloy powder was purchased from Hengbei Metal Materials Co., Ltd., sodium tripolyphosphate was purchased from Shandong Jinyou Biotechnology Co., Ltd., urotropine was purchased from Jiaozuo Runhua Chemical Industry Co., Ltd., phenolic resin was purchased from Henan Borun New Materials Co., Ltd., scandium oxide stabilized zirconia was purchased from Shanghai Mingjue Trading Co., Ltd., nano silicon carbide was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., and nano alumina was purchased from Zhuotai New Materials Technology Co., Ltd.
[0026] Example 1
[0027] This embodiment provides a water vapor resistant refractory material for a glass melting furnace and a preparation method thereof, and the specific steps are as follows:
[0028] S1. Accurately weigh 15 parts of modified fused magnesium aluminum spinel, 5 parts of modified nano titanium dioxide, 15 parts of aluminum titanate, 10 parts of scandium oxide stabilized zirconia, 10 parts of nano silicon carbide, 5 parts of nano alumina, 10 parts of zircon powder, and 3 parts of polyvinyl alcohol solution using a balance for later use;
[0029] The preparation process of the modified fused magnesium aluminate spinel is as follows: 14 g of flake graphite, 2.5 g of Al-Si alloy powder and 2 g of sodium tripolyphosphate are put into a ball mill and mixed for 30 min, 83.5 g of fused magnesium aluminate spinel is added, and the mixture is transferred to a high-speed mixer and mixed for 20 min, 8.5 g of phenolic resin and 0.6 g of urotropine are added and mixed for 15 min, and the mixture is placed in a vacuum drying oven at 60° C. for drying until the volatile content is controlled to about 0.85%, thereby obtaining the modified fused magnesium aluminate spinel.
[0030] The preparation process of the modified nano titanium dioxide is as follows: take a beaker, add 830 mL of anhydrous ethanol, place the beaker containing ethanol on a magnetic stirrer, slowly drop 170 mL of tetrabutyl titanate under the action of the magnetic stirrer, then add 1.86 g of ferrocene, stir evenly, and obtain solution A; in a flame spray pyrolysis reactor FSP (purchased from Shanghai Fuguang Precision Instrument Co., Ltd.), adjust the gas flow rate and set it to: H 2 5.3 L / min, O 25.0L / min, air 11.9L / min, and solution A was delivered at 5.0mL / min. After ignition, it burned in a hydrogen-oxygen flame to prepare modified nano-titanium dioxide.
[0031] S2, put the modified fused magnesium aluminum spinel, modified nano titanium dioxide, aluminum titanate, scandium oxide stabilized zirconium oxide, nano silicon carbide, nano alumina, and zircon powder weighed in step S1 into a ball mill and mix at 300 rpm for 1 hour, then add the polyvinyl alcohol solution and mix thoroughly in a low-speed mixer, and mix for 3 hours to obtain a mixture;
[0032] S3, pouring the mixture into an isostatic press, pressing and molding under 120 MPa, placing the mixture into a dryer for drying at 150° C. for 6 h, and curing at room temperature for 20 h to obtain a refractory body suitable for a glass kiln;
[0033] S4. Place the blank into a high-temperature tunnel kiln, raise the temperature to 1600°C at a heating rate of 4°C / min, keep it at 1600°C for 6 hours, and then cool it to room temperature at a cooling rate of 3°C / min to obtain the final water vapor resistant refractory material for glass melting furnace.
[0034] Example 2
[0035] This embodiment provides a method for preparing a water vapor resistant refractory material for a glass melting furnace, and the specific steps are as follows:
[0036] S1. Accurately weigh 17 parts of modified fused magnesium aluminum spinel, 6 parts of modified nano titanium dioxide, 17 parts of aluminum titanate, 12 parts of scandium oxide stabilized zirconia, 12 parts of nano silicon carbide, 7 parts of nano alumina, 15 parts of zircon powder, and 4 parts of polyvinyl alcohol solution using a balance for later use;
[0037] The preparation process of the modified fused magnesium aluminate spinel is as follows: 14 g of flake graphite, 2.5 g of Al-Si alloy powder and 2 g of sodium tripolyphosphate are put into a ball mill and mixed for 30 min, then 83.5 g of fused magnesium aluminate spinel is added, and the mixture is transferred to a high-speed mixer and mixed for 20 min, then 8.5 g of phenolic resin and 0.6 g of urotropine are added and mixed for 15 min, and the mixture is placed in a vacuum drying oven at 60° C. for drying until the volatile content is controlled at about 0.90%, thereby obtaining the modified fused magnesium aluminate spinel.
[0038] The preparation process of the modified nano titanium dioxide is as follows: take a beaker, add 830 mL of anhydrous ethanol, place the beaker containing ethanol on a magnetic stirrer, slowly drop 170 mL of tetrabutyl titanate under the action of the magnetic stirrer, then add 1.86 g of ferrocene, stir evenly, and obtain solution A; in a flame spray pyrolysis reactor FSP (purchased from Shanghai Fuguang Precision Instrument Co., Ltd.), adjust the gas flow rate and set it to: H2 5.3 L / min, O 2 5.0L / min and air 11.9L / min, while solution A was delivered at 5.0mL / min, and after ignition, it was burned in a hydrogen-oxygen flame to prepare modified nano-titanium dioxide.
[0039] S2, put the modified fused magnesia-aluminum spinel, modified nano-titanium dioxide, aluminum titanate, scandium oxide-stabilized zirconium oxide, nano-silicon carbide, nano-alumina, and zircon powder weighed in step S1 into a ball mill and mix at 300 rpm for 2 h, then add the polyvinyl alcohol solution in a low-speed mixer and mix thoroughly, and mix for 3.5 h to obtain a mixture;
[0040] S3, pouring the mixture into an isostatic press, pressing and molding under 120 MPa, placing the mixture into a dryer for drying at 150° C. for 6 h, and curing at room temperature for 22 h to obtain a refractory blank suitable for a glass kiln;
[0041] S4. Place the blank into a high-temperature tunnel kiln, raise the temperature to 1600°C at a heating rate of 4°C / min, keep it at 1600°C for 6 hours, and then cool it to room temperature at a cooling rate of 3°C / min to obtain the final water vapor resistant refractory material for glass melting furnace.
[0042] Example 3
[0043] This embodiment provides a method for preparing a water vapor resistant refractory material for a glass melting furnace, and the specific steps are as follows:
[0044] S1. Accurately weigh 20 parts of modified fused magnesium aluminum spinel, 8 parts of modified nano titanium dioxide, 20 parts of aluminum titanate, 15 parts of scandium oxide stabilized zirconia, 15 parts of nano silicon carbide, 10 parts of nano alumina, 20 parts of zircon powder, and 5 parts of polyvinyl alcohol solution using a balance for later use;
[0045] The preparation process of the modified fused magnesium aluminate spinel is as follows: 14 g of flake graphite, 2.5 g of Al-Si alloy powder and 2 g of sodium tripolyphosphate are put into a ball mill and mixed for 30 min, then 83.5 g of fused magnesium aluminate spinel is added, and the mixture is transferred to a high-speed mixer and mixed for 20 min, and then 8.5 g of phenolic resin and 0.6 g of urotropine are added and mixed for 15 min, and the mixture is placed in a vacuum drying oven at 60° C. for drying until the volatile content is controlled at about .95%, thereby obtaining the modified fused magnesium aluminate spinel.
[0046] The preparation process of the modified nano titanium dioxide is as follows: take a beaker, add 830 mL of anhydrous ethanol, place the beaker containing ethanol on a magnetic stirrer, slowly drop 170 mL of tetrabutyl titanate under the action of the magnetic stirrer, then add 1.86 g of ferrocene, stir evenly, and obtain solution A; in a flame spray pyrolysis reactor FSP (purchased from Shanghai Fuguang Precision Instrument Co., Ltd.), adjust the gas flow rate and set it to: H 2 5.3 L / min, O 2 5.0L / min and air 11.9L / min, while solution A was delivered at 5.0mL / min, and after ignition, it was burned in a hydrogen-oxygen flame to prepare modified nano-titanium dioxide.
[0047] S2, put the modified fused magnesia-aluminum spinel, modified nano-titanium dioxide, aluminum titanate, scandium oxide-stabilized zirconium oxide, nano-silicon carbide, nano-alumina, and zircon powder weighed in step S1 into a ball mill and mix at 300 rpm for 3 hours, then add the polyvinyl alcohol solution in a low-speed mixer and mix thoroughly and evenly, and trap the mixture for 4 hours to obtain a mixture;
[0048] S3, pouring the mixture into an isostatic press, pressing and molding under 120 MPa, placing the mixture into a dryer for drying at 150° C. for 6 h, and curing at room temperature for 24 h to obtain a refractory blank suitable for a glass kiln;
[0049] S4. Place the blank into a high-temperature tunnel kiln, raise the temperature to 1600°C at a heating rate of 4°C / min, keep it at 1600°C for 6 hours, and then cool it to room temperature at a cooling rate of 3°C / min to obtain the final water vapor resistant refractory material for glass melting furnace.
[0050] Comparative Example 1: Compared with Example 2, in this comparative example, the fused magnesia-alumina spinel is not modified in the raw material components, and the fused magnesia-alumina spinel is directly added. The rest is referred to Example 2.
[0051] Comparative Example 2: Compared with Example 2, in this comparative example, nano titanium dioxide is not modified in the raw material components, and nano titanium dioxide is directly added. The rest is the same as Example 2.
[0052] Comparative Example 3: Compared with Example 2, this comparative example is characterized in that scandium oxide stabilized zirconia is replaced by zirconium oxide in the raw material components, and the rest is the same as Example 2.
[0053] Relevant performance tests were performed on the refractory materials prepared in Examples 1-3 and Comparative Examples 1-3.
[0054] Physical performance test: Bulk density is the ratio of the mass of a material to its total volume, and apparent porosity is the percentage of the volume of all open pores in a material to its total volume. Bulk density and apparent porosity are key physical performance indicators of refractory materials. They are obtained by testing in accordance with GB / T2997-2000 "Test methods for bulk density, apparent porosity and true porosity of dense shaped refractory products".
[0055] Mechanical properties test: Room temperature compressive strength is a measure of the ultimate stress when a heat-resistant material is damaged by a pressure load at room temperature. It is an important indicator of the mechanical properties of heat-resistant materials and can reflect the compressive resistance of the material at room temperature. The room temperature compressive strength test of the sample is carried out with reference to the national standard GB / T 5072-2023 "Test method for room temperature compressive strength of refractory materials". Flexural strength Flexural strength is a measure of the ability of a heat-resistant material to resist breaking when subjected to bending force. It is another important indicator of the mechanical properties of the material, reflecting the structural integrity and durability of the material under high temperature environment. The high temperature flexural strength test of the sample is carried out with reference to the national standard GB / T 3002-2004 "Test method for high temperature flexural strength of refractory materials".
[0056] High temperature performance test: Load softening temperature is an indicator to measure the ability of heat-resistant materials to resist deformation under the combined action of high temperature and load. It reflects the structural strength of the material under high temperature environment. This article is tested according to the standard GB / T 5989-2023 "Test method for load softening temperature of refractory materials - differential heating method".
[0057] Thermal shock resistance test: Thermal shock resistance refers to the ability of heat-resistant materials to resist crack generation and expansion under rapid temperature changes. It is a comprehensive performance of the mechanical and thermal properties of materials under temperature changes. The specific operation method is to place the sample in an electric furnace at 1100℃, keep it warm for 20 minutes, take out the sample and let it cool naturally to room temperature, measure the room-temperature flexural strength of the sample after thermal shock, and calculate the residual strength retention rate of the sample to evaluate the thermal shock resistance of the sample; the calculation formula is: residual strength retention rate (%) = residual room-temperature flexural strength / original room-temperature flexural strength × 100%.
[0058] Corrosion resistance test: Corrosion resistance refers to the ability of heat-resistant materials to resist chemical corrosion in high-temperature environments, such as oxidation, sulfidation, nitridation and other corrosion forms, which is crucial to the stability of materials in high-temperature complex corrosive environments. The test was carried out in accordance with the national standard GB / T 14983-2008 "Test Method for Alkali Resistance of Refractory Materials". The sample was cut into nearly square particle samples with a side length of 3-5mm and placed in a drying oven for drying; potassium carbonate and nano carbon black were mixed evenly in a mass ratio of 1:1 as the erosion medium; the erosion medium of the same mass as the sample to be eroded was placed in a graphite crucible and compacted, and a stainless steel mesh support was placed on it to support the sample, and the sample to be eroded was placed on the support, ensuring that the crucible cover was tightened and rotated in the opposite direction for two turns; the graphite crucible containing the sample and the erosion medium was placed in a corundum sagger, covered with coke, and the corundum sagger was placed in an electric furnace, kept at 1000℃ for 10h, and naturally cooled to room temperature. The mass of the sample before and after alkali corrosion was recorded, and the mass increase rate was calculated to evaluate the corrosion resistance of the sample: the calculation formula was: mass increase rate (%) = (mass of the sample after alkali resistance test - mass of the sample before alkali resistance test) / mass of the sample before alkali resistance test × 100%.
[0059] Thermal conductivity test: Thermal conductivity (also known as thermal conductivity coefficient) refers to the amount of heat that passes through a vertical area per unit time under a unit temperature gradient. It is an important physical indicator that characterizes the thermal conductivity of refractory materials. The test is carried out in accordance with the national standard GB / T36133-2018 "Test method for thermal conductivity of refractory materials (platinum resistance thermometer method)". The sample is placed in a muffle furnace and heated to the set temperature. Local heating is performed through a linear electrical conductor (hot wire) buried in the sample along the length direction. These hot wires transmit current at a constant power, keeping the power in the length direction of the sample constant for a certain period of time. The thermal conductivity of the material is calculated by measuring the power, current and temperature change of the hot wire after a specific time interval. The calculation formula is as follows:
[0060]
[0061] Where, λ is thermal conductivity;
[0062] I——heating current;
[0063] V——voltage at both ends of the hot wire heating;
[0064] L——hot wire length;
[0065] t 1 , t 2 - the time measured after the heating current is turned on;
[0066] θ 1 ,θ 2 ——Hotline at t 1 ,t2 The corresponding temperature.
[0067] Table 1
[0068]
[0069] The test results are shown in Table 1. Figures 1 to 3 As shown in Table 1, in the tests of room temperature compressive strength, high temperature flexural strength, load softening temperature and apparent porosity: Examples 1-3 groups all showed good performance in various performance indicators, and were better than Comparative Examples 1-3 groups; among them, the refractory material of Example 2 group showed the best performance in all aspects.
[0070] In the thermal shock resistance test: the residual strength retention rate of Example 1-3 groups is significantly higher than that of Comparative Examples 1-3 groups, among which the residual strength retention rate of Example 2 group is the highest. The residual strength retention rate is an important indicator for measuring the thermal shock resistance of materials, reflecting the strength ratio that the material can maintain after being subjected to thermal shock. Materials with good thermal shock resistance have a higher residual strength retention rate after experiencing rapid temperature changes, indicating that the thermal shock resistance of Example 1-3 groups is significantly higher than that of Comparative Examples 1-3 groups, among which the thermal shock resistance of Example 2 group is the best.
[0071] In the corrosion resistance test: the mass increase rates of Example 1-3 groups are significantly lower than those of Comparative Examples 1-3 groups, among which Example 2 group has the lowest mass increase rate; since the lower the mass increase rate, the higher the stability of the material in the corrosive medium, the better the corrosion resistance of the material, indicating that the corrosion resistance of Example 1-3 groups is better than that of Comparative Examples 1-3 groups, and the corrosion resistance of Example 2 group is the best.
[0072] In the thermal conductivity test: the thermal conductivity of Example 1-3 is significantly lower than that of Comparative Example 1-3, among which the thermal conductivity of Example 2 is the lowest. Since thermal conductivity and thermal conductivity are different names for the same physical quantity, both are used to describe the ability of a material to transfer heat through a unit area per unit time under a unit temperature gradient, it shows that the thermal conductivity of Example 1-3 is lower than that of Comparative Example 1-3, and Example 2 has the lowest thermal conductivity and the lowest energy consumption.
[0073] It can be seen that the synergistic effect of modified fused magnesia-alumina spinel, modified nano-titanium dioxide, scandium oxide-stabilized zirconia and other raw material components makes the prepared refractory materials show significant advantages in multiple performance indicators. The composite effect of these components not only significantly improves the thermal shock resistance and corrosion resistance of the material, ensuring its long-term stability and structural integrity in high temperature environments, but also reduces the thermal conductivity of the material, reduces thermal damage and maintenance costs, and improves safety and production efficiency. Through this composite modification, refractory materials can more effectively cope with extreme temperature changes and erosion by corrosive media in practical applications, thereby improving overall production efficiency and extending the service life of the material.
[0074] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A water vapor resistant refractory material for a glass melting furnace, characterized in that: The refractory material comprises, by weight, 15-20 parts of modified fused magnesia-aluminum spinel, 5-8 parts of modified nano titanium dioxide, 15-20 parts of aluminum titanate, 10-15 parts of scandium oxide stabilized zirconia, 10-15 parts of nano silicon carbide, 5-10 parts of nano alumina, 10-20 parts of zircon powder and 3-5 parts of polyvinyl alcohol solution.
2. The water vapor resistant refractory material for a glass melting furnace according to claim 1, characterized in that: The preparation method of the modified fused magnesium aluminate spinel is as follows: 14 g of flake graphite, 2.5 g of Al-Si alloy powder and 2 g of sodium tripolyphosphate are put into a ball mill, mixed for 30 minutes, 83.5 g of fused magnesium aluminate spinel is added, mixed again for 20 minutes in a high-speed mixer, 8.5 g of phenolic resin and 0.6 g of urotropine are added, mixed for 15 minutes, and dried to obtain the modified fused magnesium aluminate spinel.
3. The water vapor resistant refractory material for a glass melting furnace according to claim 1, characterized in that: The preparation method of modified nano titanium dioxide is as follows: 170 mL of tetrabutyl titanate is slowly added dropwise to 830 mL of anhydrous ethanol, and then 1.86 g of ferrocene is added, and the addition process is completed on a magnetic stirrer until the mixture is stirred evenly to obtain solution A; in a flame pyrolysis reactor, hydrogen is set at 5.3 L / min, oxygen is set at 5.0 L / min, and air is set at 11.9 L / min, and solution A is delivered at 5.0 mL / min at the same time, and the solution is burned in a hydrogen-oxygen flame after ignition to prepare modified nano titanium dioxide.
4. A water vapor resistant refractory material for a glass melting furnace according to any one of claims 1 to 3, characterized in that: The specific preparation method of the material is as follows: S1. Weigh the raw materials by weight according to claim 1 and set aside; S2, putting the weighed modified fused magnesia-alumina spinel, modified nano titanium dioxide, aluminum titanate, scandium oxide-stabilized zirconium oxide, nano silicon carbide, nano alumina, and zircon powder into a ball mill and mixing them evenly, adding the polyvinyl alcohol solution and mixing them thoroughly in a low-speed mixer to obtain a mixture; S3, pouring the mixture into an isostatic press at 120 MPa, pressing and molding, and drying to obtain a green body; S4. Heat-treating the green body at 1600-1800°C for 6-8h to obtain the final refractory material.
5. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 4, characterized in that: In step S2, the raw materials are mixed in the ball mill at a rotation speed of 300 rpm for 1-3 hours.
6. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 3, characterized in that: After the mixing in step S2 is uniform, the material needs to be trapped for 3-4 hours.
7. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 4, characterized in that: The drying temperature in step S3 is 150° C. and the drying time is 6 hours.
8. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 4, characterized in that: After drying in step S3, curing at room temperature for 20-24 hours is required.
9. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 4, characterized in that: The heating rate during the heat treatment in step S4 is 4°C / min, and the cooling rate is 3°C / min.
10. The method for preparing a water vapor resistant refractory material for a glass melting furnace according to claim 4, characterized in that: The heat treatment process in step S4 needs to be performed under nitrogen protection.
Citation Information
Patent Citations
Refractory brick used for oxygen-fuel combustion glass kiln
CN102992782A
Refractory material for glass kiln as well as preparation method and application of refractory material
CN118324485A
Refractory material, and waste incinerating / melting furnace
JP2007131495A
High-strength melting furnace for non-ferrous enhanced smelting
WO2020168885A1
Cited By
Ultrahigh-temperature-resistant high-speed jet material for vehicle-mounted fluid director of spaceflight launching site and construction process
CN119930308A
Nano boron nitride / magnesium aluminate spinel composite powder additive and preparation method thereof
CN120504547A